2001
DOI: 10.1271/bbb.65.466
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curdlan Increases Proliferation of Bifidobacteria in The Cecum of Rats

Abstract: Significant increases in the amounts of short-chain fatty acids and lactate, and in numbers of bifidobacteria were observed in the cecum of curdlan (CD) -fed rats as compared with those of cellulose-fed ones. The in vitro proliferation of 5 species of bifidobacteria was markedly increased in the cultures containing the supernatant obtained from the cecal contents of CD-fed rats. These findings suggest that bifidus factors have been produced in the cecum of CD-fed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…In vitro and animal trials support that high barley ␤-glucan consumption is associated with a significant increase in the synthesis of SCFA (46,49,50). This study confirmed the previous GC-MS data showing a noticeable increase in 2-methyl-propanoic acid, acetic acid, butanoic (butyric) acid, and propanoic (propionic) acid after the diet intervention with durum wheat flour and whole-grain barley pasta.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In vitro and animal trials support that high barley ␤-glucan consumption is associated with a significant increase in the synthesis of SCFA (46,49,50). This study confirmed the previous GC-MS data showing a noticeable increase in 2-methyl-propanoic acid, acetic acid, butanoic (butyric) acid, and propanoic (propionic) acid after the diet intervention with durum wheat flour and whole-grain barley pasta.…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, oat ␤-glucans did not favor the growth of Clostridium sp. in SHIME and C57BL/6J mouse models (21,24,49). However, several discrepancies between the different studies might be due to the different models and methods used.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation of b-glucan fractions from barley and oats by human faecal microbiota induced high clostridial cluster IX populations and a significant increase in Clostridium histolyticum subgroup (Hughes et al, 2008). On the contrary, oat bran feeding in SHIME model and curdlan diets in rat experiments did not favor the growth of Clostridium spp., respectively Shimizu et al, 2001).…”
Section: Tablementioning
confidence: 99%
“…Bifidobacteria have been cultured from the cecal contents of chickens (31,35,51), rats (43), rabbits (20,35,46), pigs (37), and humans (21). Isolates were confirmed as belonging to the genus Bifidobacterium in all but the rat and pig studies, through the detection of fructose-6-phosphate phosphoketolase (F-6-PPK) (41).…”
mentioning
confidence: 99%